Beethoven's storm - Pickardt, Ernst, 1876-1931 (artist):::Creator:::::::::::: (Germany)
Portrait etching of Beethoven by Pickardt titled "Beethoven's storm." Hand signed by the artist in pencil. Signature also etched into the plate.